Trapping evidence for the thermal cyclization of di-(o-acetylphenyl)acetylene to 3,3'-dimethyl-1,1'-biisobenzofuran - Casey, Charles P.; Strotman, Neil A.; Guzei, Ilia A. (Beilstein Journal of Organic Chemistry, 2005)
The reaction of di-(o-acetylphenyl)acetylene (1) with excess dimethyl acetylenedicarboxylate (DMAD) produced bis-DMAD adducts meso-3 and rac-3. This transformation is suggested to involve thermal rearrangement of 1 to the intermediate 3,3'-dimethyl-1,1'-biisobenzofuran (A), and subsequent Diels-Alder cycloadditions of two equivalents of DMAD to A. The isolation of trapping products meso-3 and rac-3, which contain complex polycyclic frameworks, provide strong evidence for the transient production of A, the first biisobenzofuran. An X-ray crystal structure of meso-3 was obtained.